2017
DOI: 10.2174/1871526517666170116142547
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salivary Vitamin C and Catalase in HIV Positive and Healthy HIV Negative Control Group

Abstract: HIV can alter salivary antioxidant capacity as well as vitamin C and catalase levels. Saliva may reflect serum antioxidative changes in these patients. Therefore, further research is necessary on salivary and serum oxidants and the antioxidant changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From the results, they concluded that salivary antioxidant capacity could be altered by HIV. 18 Nosratzehi et al 15 assessed and compared the cotinine levels in the saliva of hookah smokers, nonsmokers, and passive smokers. They analyzed a total of 150 subjects, of which 50 were passive smokers, 50 were nonsmokers, and remaining 50 were hookah smokers.…”
Section: Discussionmentioning
confidence: 99%
“…From the results, they concluded that salivary antioxidant capacity could be altered by HIV. 18 Nosratzehi et al 15 assessed and compared the cotinine levels in the saliva of hookah smokers, nonsmokers, and passive smokers. They analyzed a total of 150 subjects, of which 50 were passive smokers, 50 were nonsmokers, and remaining 50 were hookah smokers.…”
Section: Discussionmentioning
confidence: 99%
“…It can increase in hypoxia due to the appearance of oxidant metabolites and there is evidence that salivary UA is altered in diseases such as oral lichen planus or diabetes ( 13 , 16 ). Catalase is an enzyme capable of removing ROS from saliva and its activity is altered in patients with different diseases such as human immunodeficiency virus ( 17 ). Components of the oxidant system can also be measured in saliva, namely the advanced oxidation protein products (AOPP) and hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%